Hypoxia-induced Slug SUMOylation enhances lung cancer metastasis - Hung, Pei-Fang (J Exp Clin Cancer Res, 2019)
BACKGROUND: The Slug-E-cadherin axis plays a critical role in non-small-cell lung cancers (NSCLCs) where aberrant upregulation of Slug promotes cancer metastasis. Now, the post-translational modifications of Slug and their regulation mechanisms still remain unclear in lung cancer. Hence, exploring the protein linkage map of Slug is of great interest for investigating the scenario of how Slug protein is regulated in lung cancer metastasis. METHODS: The Slug associated proteins, Ubc9 and SUMO-1, were identified using yeast two-hybrid screening; and in vitro SUMOylation assays combined with immunoprecipitation and immunoblotting were performed to explore the detail events and regulations of Slug SUMOylation. The functional effects of SUMOylation on Slug proteins were examined by EMSA, reporter assay, ChIP assay, RT-PCR, migration and invasion assays in vitro, tail vein metastatic analysis in vivo, and also evaluated the association with clinical outcome of NSCLC patients. RESULTS: Slug protein could interact with Ubc9 and SUMO-1 and be SUMOylated in cells. Amino acids 130–212 and 33–129 of Slug are responsible for its binding to Ubc9 and protein inhibitor of activated STAT (PIAS)y, respectively. SUMOylation could enhance the transcriptional repression activity of Slug via recruiting more HDAC1, resulting in reduced expression of downstream Slug target genes and enhanced lung cancer metastasis. In addition, hypoxia could increase Slug SUMOylation through attenuating the interactions of Slug with SENP1 and SENP2. Finally, high expression Slug and Ubc9 levels were associated with poor overall survival among NSCLC patients. CONCLUSIONS: Ubc9/PIASy-mediated Slug SUMOylation and subsequent HDAC1 recruitment may play a crucial role in hypoxia-induced lung cancer progression, and these processes may serve as therapeutic targets for NSCLC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13046-018-0996-8) contains supplementary material, which is available to authorized users.